Against vowel length in Tigrinya - Eugene Buckley (LibraryPress@UF, 1997)
The premise of this paper is that vowel length plays no role in the synchronic phonology of Tigrinya: processes affecting vowels should be treated in qualitative terms only. The evidence in favor of synchronic vowel length is weak, and stronger evidence favors an analysis in which vowel length is phonologically irrelevant. While some researchers have made use of contrastive vowel length in the modern language to account for ostensible closed-syllable shortening, the analysis presented here shows that the relevant alternations are very limited in scope and represent at best the residue of historical vowel length. The evidence presented includes word minimality, vowel coalescence, wordfinal fronting, guttural lowering, and low dissimilation, with analyses of these phenomena in purely featural terms.